The size of the digital economy in Finland and its impact on taxation - Jyrki Ali-Yrkkö; Heli Koski; Otto Kässi; Mika Pajarinen; Tarmo Valkonen; Marja Hokkanen; Noora Hyvönen; Elina Koivusalo; Jarno Laaksonen; Juha Laitinen; Enni Nyström (The Research Institute of the Finnish Economy (ETLA), 2020)
This report sheds light on the size and composition of the digital economy in Finland and its impact on the tax gap and tax system. No generally agreed definition of digital economy exists, and only a few prior studies have assessed the size of the digital economy quantitatively. We measured the size of the digital economy by the value added generated by digitally produced goods and services. We first replicated the analysis of the US Bureau of Economic Analysis (BEA) using Finnish data by assessing the value added of fully digital products. Secondly, we also took into account in our calculations the value added of partly digital products. Our analysis shows that the share of value added generated by the digital economy in Finland has grown at a relatively slow pace during the 2010s. Our calculations indicate that the digital economy comprised 10.9% of the GDP in Finland in 2017, or over EUR 21 billion euros. We further aimed at assessing the size of the corporate income tax (CIT), the value added tax (VAT) and the personal income tax (PIT) gaps generated by the digital economy in Finland. An attempt to make a full CIT gap analysis failed due to the unavailability of industry-level national accounts data. Data on the accrued VAT from the most recent years was not available but the observations from the earlier years did not reveal tax gaps. Our data collected via a survey targeted at digital freelance workers hints that, in general, Finnish digital freelancers comply with taxation rather well and no notable PIT tax gap is generated.
Keywords: H2; H26; O33; O5; 330; Digitalization; Digital economy; Taxation; Tax gap